142 Improving Functional Outcomes During Covid-19 for Both COVID-19 and Non COVID-19 Positive Older Adults Through the Introduction. (16th March 2021) - Roberts, F; Birmingham, K; Darlison, L; Hertzberg, K; Chapman, K; Krampikowski, J; Bunden, D; King, L; Tebbutt, E; Potter, E
Abstract: Purpose: To improve the functional outcomes of older adults presenting to the Health and Ageing wards during the COVID-19 pandemic through a focussed rehabilitation list. The intended benefits to the older adult and service were for: 1. Daily rehabilitation input for older adults. 2. Older adults to spend less time immobile. 3. Ongoing rehabilitation intervention while awaiting medical clearance for discharge. 4. Increased staff satisfaction 5. Better outcomes on discharge. 6. Rehabilitation ethos on the Health and Ageing wards. Methods: The quality improvement project was carried out using the Plan, Do, Study, Act (PDSA) cycle. Three iterative PDSA cycles were carried out over the course of the project to deliver proactive interventions as a result of analysis of baseline data and stakeholder involvement. These interventions were aimed at developing communication around the rehabilitation list within the team and sustainability of this list. Results: The project resulted in better functional outcomes for older adults and increased staff morale. Between May 2020–June 2020, a total of 56 patients were seen on the rehabilitation list, with 84% of these patients seeing improvements in their Elderly Mobility Scores (EMS). 27% of patients on the rehabilitation list saw a change to their initial discharge plan, either needing reduced packages of care or reduced need for ongoing rehabilitation in an external setting. Conclusions: The quality improvement project found that with focussed rehabilitation older adult inpatients with or without COVID-19 can make significant functional gains. These gains have wider effects on their outcomes on discharge and also for the service through increased morale and job satisfaction. Due to demand and capacity issues in the acute setting, older adults who would often benefit from ongoing input are not always reviewed regularly. This project demonstrates that with focussed rehabilitation older adults can improve and achieve better functional outcomes.